Global Psychologies Mental Health and the Global South (Palgrave Macmillan UK, 2018)
This book critiques our reliance on Eurocentric knowledge in the education and training of psychology and psychiatry. Chapters explore the diversity of 'constructions of the self' in non-Western cultures, examining traditional psychologies from Africa, Asia, Australasia, and Pre-Columbian America. The authors discuss liberation psychologies and contemporary movements in healing and psychological therapy that draw on both Western and non-Western sources of knowledge. A central theme confronted is the importance, in a rapidly shrinking world, for knowledge systems derived from diverse cultures to be explored and disseminated equally. The authors contend that for this to happen, academia as a whole must lead in promoting cross-national and cross-cultural understanding that is free of colonial misconceptions and prejudices. This unique collection will be of value to all levels of study and practice across psychology and psychiatry and to anyone interested in looking beyond Western definitions and understandings. .